Fuel cell behavior and energy balance on board a Hyundai Nexo. (May 2022) - Sery, Jules; Leduc, Pierre
Hydrogen fuel consumption measuring methodologies of a fuel cell vehicle without modifying the fuel path has been tested and benchmarked. In this work, they are applied to a Hyundai Nexo fuel cell electric vehicle driving different mission profiles on a chassis dynamometer. Three methods respectively based on hydrogen tank pressure, tailpipe oxygen concentration, and IR-shared (infrared) tank data are compared to the reference method relying on fuel cell current measurements. In addition to the hydrogen fuel consumption results, the installed electrical measuring equipment made possible to yield the fuel cell efficiency map at both stack and system levels as well as the energy consumption of its balance-of-plant (BoP) components during steady-state operation. A maximum steady-state efficiency of 66.8% is reported along with a rated system power of 82 kWe involving a 9.1-kWe power consumption for the electric compressor. It is shown that the compressor and the 12-V accessories are the most energy consuming devices among the BoP components accounting for 2%–3% of the total electric energy generated by the fuel cell. Furthermore, the behavior of the powertrain system is monitored and discussed during warm-up phases and during a long idling period. Finally, based on non-intrusive temperature measurements, a short analysis is conducted about the temperature impact on the fuel cell efficiency.